Kritik Sosial dalam Siber Sastra Monolog Whynesia pada Kanal Youtube Tretan Universe - Syahala Fizky Alrhychard; Onok Yayang Pamungkas (Pusat Riset dan Inovasi Nasional, 2023)
This research seeks to find out how social criticism is in cyber literature, the Whynesia monologue on the Tretan Universe YouTube channel. This research method uses descriptive qualitative methods. The data used are three cyber videos of Whynesia monologue literature on the Tretan Universe YouTube channel. This research data was collected using the listening and note-taking method. The results of the research show that Whynesia's cyber literary monologue on the Tretan Universe YouTube channel has deep social criticism regarding the phenomena currently occurring. Through the flow of the monologue delivered, the narrator presents a discourse of social criticism regarding social problems that occur in Indonesia. This monologue presents the importance of social criticism which acts as a tool to maintain societal stability. Strong and courageous monologues in conveying criticism, stimulate thinking about the importance of creating stable conditions in society, where people must express their voice or social criticism regarding problems in the environment. The implication of the findings is the importance of social criticism to maintain the stability of society and the importance of new media such as research objects to revive literary works as a medium for social criticism. Therefore, society must fight so that existing inequalities or problems can be voiced to create stability and regeneration of literary works as a medium used in society.